Caddie Woodlawn - Brink, Carol Ryrie, 1895-1981. (New York : Aladdin Paperbacks, 1997)
Chronicles the adventures of eleven-year-old Caddie growing up with her six brothers and sisters on the Wisconsin frontier in the mid-nineteenth century.
Newbery Medal/Honor.
School Library Journal.
Wilson's Children.
Book Links (A.L.A.), November 1995.
Booklist, April 1997.
Child Study Children's Book Committee, August 2007.
Keywords: Brothers and sisters -- Fiction; Frontier and pioneer life -- Wisconsin -- Fiction; Frontier and pioneer life -- Wisconsin -- Fiction; Siblings -- Fiction; Wisconsin -- Fiction; Wisconsin -- Fiction